2013
DOI: 10.1097/mcg.0b013e3182705f9e
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Prognosis of the Jejunal Involvement of Crohn’s Disease

Abstract: Korean CD patients are more likely to have jejunal involvement than western patients. Jejunal involvement is one of the poor prognostic factors in Korean CD patients, as it is in westerners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 46 publications
1
50
1
Order By: Relevance
“…Clinically, the superior sensitivity of VCE for proximal small bowel disease represents an important diagnostic advantage because proximal small bowel disease has recently been demonstrated to be a significant negative prognostic factor in CD in several studies. [21][22][23] …”
Section: Vce Versus Other Modalities For the Diagnosis Of CDmentioning
confidence: 98%
“…Clinically, the superior sensitivity of VCE for proximal small bowel disease represents an important diagnostic advantage because proximal small bowel disease has recently been demonstrated to be a significant negative prognostic factor in CD in several studies. [21][22][23] …”
Section: Vce Versus Other Modalities For the Diagnosis Of CDmentioning
confidence: 98%
“…In the remaining 35-50% of patients, disease affects the ileocolonic area [2,3]; thus, the small bowel is affected in 70-80% of patients. Nowadays, there is evidence that up to 20% of patients with known CD have isolated jejunal involvement, although the exact frequency is not known [4][5][6][7]. Because of nonspecific symptoms and the absence of a gold-standard diagnostic method, the diagnosis of CD can be delayed for months [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…55 Jejunal involvement has been recognized as an independent marker of severity in CD, being associated with an increased risk of relapse, 55 higher use of corticosteroids (HR 1.24; 95% CI: 1.02 -1.50) and thiopurines (HR 1.26; 95% CI: 1.06 -1.49), higher rates of strictureplasties (RR 2.52; 95% CI: 1.60 -3.96), hospitalizations (RR 1.29; 95% CI: 1.14 -1.47), and longer hospitalization duration (RR, 1.30; 95% CI, 1.25 -1.34). 56 Recently, it was reported that treatment with thiopurines and/or biologics was started more often in patients with proximal small bowel lesions detected by SBCE [13/33 (39%) vs 1/17 (6%), p = 0.011, relative risk (RR) 6.5], particularly when severe (6%, 36% and 45% of patients with non-significant, mild and moderate-to-severe inflammation, respectively).…”
Section: Crohn's Diseasementioning
confidence: 99%